Comparação de características familiares de crianças público alvo da educação especial com diferentes faixas etárias - Santos, Luciana Stoppa dos (2014)
This study aimed to investigate the impact of family variables in the development cycle of a child PAEE over time. 45 fathers or mothers of special education target audience children participated in the survey, aged from one to ten years attending early stimulation, specialized education and / or the regular school services. Data collection took place at the place of parental preference or inside the institutions. To obtain the information, the participants were divided by age composing the following groups: G1 - parents of children from zero to three years old, G2 - parents of children from three to six years old and G3 - parents of children from six to ten years old. Participants responded to the following instruments: ( a) semi-structured interviews , ( b ) Resources and Stress Brief Questionnaire, ( c ) Questionnaire on the needs of families - QNF (d ) EC- Home Inventory , ( e) Scale of family empowerment , ( f ) Inventory of resources of the family environment ( RAF ) and ( g ) Social Support Questionnaire ( QSS ) . Data from each group were analyzed separately, for the interview data were used descriptive analyzes and for the standardized instruments data were estimated averages and standard deviations. To compare the data of the three groups was used the ANOVA test and to relate the family variables the Pearson correlation test was applied. The results demonstrated that parents from G1 showed higher levels of stress when compared with parents from G2 and G3 and G2 and G3 parents were more empowered than parents from G1. Higher the level of stress in families of the three groups, higher the needs in different levels, and higher levels of stress also undermined quality and quantity of stimulation offered. Relative to social support, the most mentioned people acting as supporters were the parents and the spouse and the G3 was the group that had the highest average number of people who offered support in different situations. Regarding qualitative data, the majority of parents reported that their children attended early stimulation services and highlighted the relevance of this assistance for the children development. It was also noted that parents had an intense interest in daily care routine and monitoring children in the specialized assistance. Only a few participants reported that other family members assisted in daily care, pointing that the majority only participate playing or cosseting the children. Finally, parents from G1, G2 and G3 groups showed responses that indicate the importance of support / specific support (emotional, informational) for themselves and for other family members.